Determinants of Self-initiated Expatriation. The Paradox of International Faculty Migration to Moroccan Universities - Rachid Alami Aroussi; Marc Poulin; Rommel Sergio (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study seeks to highlight key motivational influences for international faculty self-initiated expatriation (SIE) from developed to developing countries. We use the North African country of Morocco as a case illustration. While previous research has focused extensively on south-to-north migration, scant attention has been given to the migration of academic faculty from developed to developing regions despite the increasing level of activity in this area. Against this backdrop, this study provides fresh insights into the push and pulls factors—notably the motivations, expectations, and experiences of faculty who have embarked upon this type of mobility and drawing upon the theoretical lens of SIE. The study revealed that non-economic factors, namely ‘gaining international experience’, ‘raising academic status’ and ‘greater employment opportunities’ are the most important pull factors to migrate while ‘lack of career opportunities’, ‘unsatisfied job’ and ‘underemployment’ are the push factors that influence faculty self-initiated expatriation to Morocco. Our study showed 53.1% overall job satisfaction among expatriates while literature reported unsatisfactory career development and work conditions among local university teachers. Findings attested that expatriate women, in the large majority (89.3%), were unsatisfied with their current job while, on the contrary, men are globally contented (68%). Active local professional network seems to have a significant correlation with expatriate men’s job satisfaction.